Wolbachia is not all about sex: male-feminizing Wolbachia alters the leafhopper Zyginidia pullula transcriptome in a mainly sex-independent manner - Asgharian, Hosseinali; Chang, Peter L.; Mazzoglio, Peter J.; Negri, Ilaria (Frontiers in Microbiology, 2014)
Wolbachia causes the feminization of chromosomally male embryos in several species of crustaceans and insects, including the leafhopper Zyginidia pullula. In contrast to the relatively well-established ecological aspects of male feminization (e.g., sex ratio distortion and its consequences), the underlying molecular mechanisms remain understudied and unclear. We embarked on an exploratory study to investigate the extent and nature of Wolbachia's effect on gene expression pattern in Z. pullula. We sequenced whole transcriptomes from Wolbachia-infected and uninfected adults. 18147 loci were assembled de novo, including homologs of several Drosophila sex determination genes. A number of transcripts were flagged as candidate Wolbachia sequences. Despite the resemblance of Wolbachia-infected chromosomal males to uninfected and infected chromosomal females in terms of sexual morphology and behavior, principal component analysis revealed that gene expression patterns did not follow these sexual phenotype categories. The principal components generated by differentially expressed genes specified a strong sex-independent Wolbachia effect, followed by a weaker Wolbachia-sexual karyotype interaction effect. Approaches to further examine the molecular mechanism of Wolbachia-host interactions have been suggested based on the presented findings.